Religion, Family Pressure, Life Conditions: Turkish Female Foreign Fighters in Their Own Words - Öztop, Fatma Anıl (Terrorism and political violence, 2024)
The article aims to contribute to the discussion why and how women join violent extremist groups by exploring the motivational factors among Turkish ISIS women, zooming in on the level of agency in their decision. Our focus was on Turkish women as there have been no previous studies of this cohort. We used thematic analysis of the transcripts from interviews with thirty-seven Turkish ISIS women. Our analysis revealed three main motivational factors: religion, family pressure, and escaping life conditions. The first main finding of the study is that the twenty-two women who viewed religion as more than a belief were motivated by political and ideological factors and had agency and choice. Secondly, the twelve women who are motivated by family pressure continued to strictly adhere to their traditional roles as dutiful daughters or dutiful wives to their militant fathers or husbands. Thirdly, the three women who often emphasized the oppressive conditions under which they lived and a desire to gain independence and wanted to be accepted, respected, and valued prioritized escaping current life conditions. The study indicates that Turkish ISIS women are driven by different motivational factors and that most of the women in the study made a rational choice to join ISIS, be it out of political or ideological motivations or to escape oppression. In this context, the findings reported here shed light on the fact that women, like men, may resort to violence as the best means of achieving their political purpose.